Isolation of living sperm cells and in vitro fusion of Torenia fournieri gametes - Vági, P.; Imre, K.; Kristóf, Z. (International Journal of Horticultural Science, 2006)
In contrast to most angiosperms, Torenia contains a naked embryo sac and therefore has been considered since many years as an exciting model plant to study the double fertilization process of flowering seed plants. It is thus not surprising that the isolation of protoplasts from the female gametophyte has been reported already 20 years ago by Mol, the isolation of megaspores and megagametophytes has been published by the authors of this manuscript in 1996 and in 1999. The isolation of the male gametophyte and of sperm cells was published by the authors in 2004. The isolation of viable Torenia sperm cells is a crucial part of the elaboration of an in vitro fertilization system. Torenia sperm cells were isolated from in vivo — in vitro cultured pollen tubes. In this system pollen tubes first grow inside a cut style then follow their elongation in a solid isolation medium. The medium contained agarose in order to detain pollen tube contents. Released sperm cells and enzymatically isolated egg cells were collected and handled using glass micropipettes and transmitted to an electrofusion apparatus or polyethylene glycol containing media for fusion probes.